The Effect of Hedonic Shopping Motivation, Shopping Lifestyle, and Fashion Involvement on Impulse Buying on Zalora Customers in Medan City - Annisa Edelia; Tuti Anggraini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to analyze the direct effect of Hedonic Shopping Motivation, Shopping Lifestyle and Fashion Involvement on Impulse Buying. The population of this research is Zalora's customers in Medan city. With an unknown population, Bernoulli's formula is used and the number of samples is 60 respondents by purposive sampling. The data was obtained by using a google form questionnaire. The data analysis method used is associative statistical analysis and Partial Least Square (SEM-PLS) 3.0 analysis. Data collection techniques using a Google form questionnaire. The results showed that the Hedonic Shopping Motivation had a significant effect on Impulse Buyingvariable Shopping Lifestyle had a significant effect on Impulse Buying variable Fashion Involvement had a significant effect on Impulse Buying.